Students’ learning difficulties based on cognitive level of excretory system material - Syarif Rizalia; Sesar Nopriansyah; Muhammad Saefi; Widi Cahya Adi; Eka Damayanti; S. Sukmawati (University of Muhammadiyah Malang, 2024)
The biology material on the excretory system has a high level of learning difficulty, including the complexity of the material and the high level of abstraction, which can affect students' learning process and outcomes. Therefore, it is necessary to analyze the internal and external sources causing learning difficulties by conducting research that aims to interpret: 1) the level of students' learning difficulties based on the cognitive level of the excretory system material, 2) the factors causing students' learning difficulties based on the cognitive level of the excretory system material. This research is a qualitative study using an ex post facto method conducted at SMA Negeri 2 Konawe Selatan. The subjects of this research are 56 Grade XI students who experience learning difficulties, and the biology teacher. The data collection techniques used are: 1) tests, which were analyzed descriptively statistically; 2) interviews, which were analyzed through four stages: collection, reduction, display, and conclusion, followed by testing the validity of the data through triangulation. The results of this research show that: 1) Students' learning difficulties viewed from the cognitive levels of each learning indicator on the excretory system material are generally categorized as slightly difficult with a percentage of 58.93%; 2) The factors causing students' learning difficulties are students' interest in learning, students' habits during the learning process, evaluation techniques, as well as family, school, and community environmental aspects.